ADVANTAGES OF BILINGUALISM IN PRESCHOOL EDUCATION - Dilnoza Fozilova (American Journals, 2024)
This article purposes to discuss about the importance of bilingualism, beneficial sides of bilingualism in early childhood and children’s future life. Furthermore there is a research presented as a questionnaire. The research study was conducted among 70 kindergarten teachers of Uzbekistan. Research question: which benefits of bilingualism are admitted by kindergarten teachers ?
Keywords: Bilinguall, bilingualism, kindergarten teachers, children, peers, questionnaire